Plasticity of patient-matched normal mammary epithelial cells is dependent on autologous adipose-derived stem cells - Kengelbach-Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Schmid, Rafael; Marques, Jasmin Monteiro; Beier, Justus; Beckmann, Matthias; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Scientific Reports, 2019)
Due to the increasing clinical application of adipose-derived stem cells (ADSC), e.g. lipotransfer for breast reconstruction, this study aimed to gain novel insights regarding ADSC influence on breast tissue remodeling and determine patient-dependent factors affecting lipotransfer as well as begin to address its oncological risks. The ADSC secretome was analyzed from five normal breast reduction patients and contained elevated levels of growth factors, cytokines and proteins mediating invasion. ADSC/ADSC secretomes were tested for their influence on the function of primary mammary epithelial cells, and tumor epithelial cells using cell culture assays. ADSC/ADSC secretomes significantly stimulated proliferation, transmigration and 3D-invasion of primary normal and tumor epithelial cells. IL-6 significantly induced an EMT and invasion. The ADSC secretome significantly upregulated normal epithelial cell gene expression including MMPs and ECM receptors. Our study supports that ADSC and its secretome promote favorable conditions for normal breast tissue remodeling by changing the microenvironment. and may also be important regarding residual breast cancer cells following surgery.
CRIS-Team Scopus Importer:2019-08-06